2016
DOI: 10.1016/j.biocon.2016.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Thermally buffered microhabitats recovery in tropical secondary forests following land abandonment

Abstract: Given the dramatic loss of tropical forests and accelerating climate change, secondary forest regeneration is increasingly recognised as being an important method for reversing losses in biodiversity and carbon stocks. The recolonisation of biodiversity within secondary forests depends upon the recovery of forest structure, including the range of microhabitats used by diverse communities. Here, we investigate the return of critical microhabitats along a successional gradient of secondary forest in the Tropical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 82 publications
1
43
0
Order By: Relevance
“…Many ectotherms, such as amphibians, spend some or all of their time exploiting cool microclimates inside microhabitats, which thermal images are unable to capture. We selected three types of microhabitat known to provide cool microclimates (González del Pliego et al., ; Scheffers, Brett et al., ; Scheffers, Evans et al., ), and placed one temperature datalogger (HOBO pendant datalogger, Onset, model UA‐001‐64K or model UA‐002‐64K) per plot in each microhabitat type: deadwood (>10 cm stem diameter), tree holes (>2 cm at widest point of entrance hole, <2 m above the ground) and leaf litter (1.5 m left of the plot centre). The hygrometer measurements of macroclimate temperature were not always synchronized with the dataloggers inside microhabitats, hence we additionally measured macroclimate temperature using a datalogger suspended 1.5 m above the ground at the centre of each plot, shielded against direct radiation and precipitation by an inverted plastic funnel (Scheffers, Brett et al., ; Shoo, Storlie, Williams, & Williams, ).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Many ectotherms, such as amphibians, spend some or all of their time exploiting cool microclimates inside microhabitats, which thermal images are unable to capture. We selected three types of microhabitat known to provide cool microclimates (González del Pliego et al., ; Scheffers, Brett et al., ; Scheffers, Evans et al., ), and placed one temperature datalogger (HOBO pendant datalogger, Onset, model UA‐001‐64K or model UA‐002‐64K) per plot in each microhabitat type: deadwood (>10 cm stem diameter), tree holes (>2 cm at widest point of entrance hole, <2 m above the ground) and leaf litter (1.5 m left of the plot centre). The hygrometer measurements of macroclimate temperature were not always synchronized with the dataloggers inside microhabitats, hence we additionally measured macroclimate temperature using a datalogger suspended 1.5 m above the ground at the centre of each plot, shielded against direct radiation and precipitation by an inverted plastic funnel (Scheffers, Brett et al., ; Shoo, Storlie, Williams, & Williams, ).…”
Section: Methodsmentioning
confidence: 99%
“…In primary forests and secondary forests re‐growing on abandoned farmland, previous studies found that organisms—particularly ectotherms—avoid suboptimal temperatures in the wider “macroclimate” (climate at a spatial scale of m to ha) by moving locally into “microclimates”: climate at a fine‐scale, mm to m, that is distinct from the macroclimate (González del Pliego et al., ; Scheffers, Brett, Diesmos, Williams, & Evans, ; Scheffers, Evans, Williams, & Edwards, ). Climate at this fine‐scale is more relevant for the majority of terrestrial biodiversity, which primarily consists of small‐bodied ectotherms (Nadeau, Urban, & Bridle, ; Potter, Arthur Woods, & Pincebourde, ; Suggitt et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations